Improving Students' Reading Comprehension of Descriptive Text by Using KWL (KNOW-WANT-LEARN) Strategy at SMPN 9 Banjarbaru, Kalimantan Selatan - Sari Lolyta Engelina (Graduate Program, University of Islam Malang, 2021)
ABSTRACTEnglish language has basic skills; speaking, reading, writing, and listening. One of these basic skills which is still difficult and complicated for the students to learn is reading. Some problems which could be found in reading are: (1) finding the meaning of new words, (2) the lack of vocabulary, (3) less motivation, and (4) less interest in learning English. The researcher thought that through KWL (KNOW-WANT-LEARN) Strategy, the students’ can improve their Reading Comprehension of Descriptive Text of animals. The research answered this main question: How can 32 students of VIII F Class at SMPN 9 Banjarbaru in academic year 2016/2017 improve their Reading Comprehension of Descriptive Text through KWL Strategy?Research methodology was conducted by using Classroom Action Research (CAR) that was done from October 26 to November 10, 2016 in even semester of academic year 2016/2017 of SMPN 9 Banjarbaru, Kalimantan Selatan which involved 32 students of VIII F Class.There were two cycles used in this research and each cycle consists of planning, acting, observing, and reflecting. The result indicated that there is an improvement of students’ reading comprehension of descriptive text by using KWL Strategy. It can be seen from: (1) the students’ behavior in paying attention in teaching and learning, (2) participation of students’ who were active, (3) enthusiastic of students’ activity in reading, (4) score result of Initial Reflection (IR) was 52.34, (5) Reflection result of (X1), (X2), (X3), and (X4) were 59.69, 67.19, 75.00, and 82.19 which showed the progress of Students in Reading Comprehension of Descriptive Text by Using KWL Strategy. It can be concluded that implementation of KWL Strategy in reading comprehension of descriptive text is effective and appropriate for the students to improve their reading comprehension.